'Not only faces': specialized visual representation of human hands revealed by adaptation. Issue 12 (16th December 2020) - Conson, Massimiliano; Polito, Francesco; Di Rosa, Alessandro; Trojano, Luigi; Cordasco, Gennaro; Esposito, Anna; Turi, Marco
Abstract : Classical neurophysiological studies demonstrated that the monkey brain is equipped with neurons selectively representing the visual shape of the primate hand. Neuroimaging in humans provided data suggesting that a similar representation can be found in humans. Here, we investigated the selectivity of hand representation in humans by means of the visual adaptation technique. Results showed that participants' judgement of human-likeness of a visual probe representing a human hand was specifically reduced by a visual adaptation procedure when using a human hand adaptor but not when using an anthropoid robotic hand or a non-primate animal paw adaptor. Instead, human-likeness of the anthropoid robotic hand was affected by both human and robotic adaptors. No effect was found when using a non-primate animal paw as adaptor or probe. These results support the existence of specific neural mechanisms encoding human hand in the human's visual system.